LBSN 2011 Workshop Report: The 3rd ACM SIGSPATIAL International Workshop on Location-Based Social Networks - Zheng, Yu; Mokbel, Mohamed F. (ACM SIGSPATIAL, 2012)
Social networks have been prevalent on the Internet, attracting many professionals from a variety of fields. By adding a location dimension, we can bring online social networks back to the physical world and share our real-life experiences in the virtual world conveniently. In Location Based Social Networks (LBSN), people cannot only track and share location-related information with each other via either mobile devices or desktop computers, but also leverage collaborative social knowledge learned from user-generated and location-related contents. As location is one of the most important properties in people’s daily lives, LBSN will bridge the gap between online societies and the physical world and enable a lot of novel applications changing the way we live, such as travel planning, location/friend recommendations, community discovery, human mobility modeling and user activity analysis. The technology derived from LBSN, e.g., location trajectory mining and retrieval, can also be applied to a multitude of other research areas including biology, sociology, geography, and climatology, etc. The objective of this workshop is to provide professionals, researchers, and technologists with a single forum where they can discuss and share the state-of-the-art of LBSN development and applications, present their ideas and contributions, and set future directions in emerging innovative research for location based social networks.